Study on bioethanol production from oil palm trunk SAP - Nurul Ain , Jalanni (2010)
Old oil palm trunk becomes a promising source of sugars by proper aging after logging and,thus,its sap can be a good feedstock for bioethanol.It aims to develop alternative resources waste to wealth for bio-ethanol production using available biomass in this country.To produce high production of bioethanol,determine fermentation conditions are important in culture fermentation to predict the optimum temperature and optimum inoculums size.The process selection includes preparation of pure culture,yeast activation, fermentation profile,and validation between two types of yeast, batch fermentation and analysis of the data.The overall process performance is measured by the productivity and quality of bioethanol produced.Glucose was thoroughly nearly consumed after 48 hour for the fermentation profile. Validation experiment between showed that Saccharomyces cerevisiae Kyokai 7 produce high yield of ethanol.The effects of temperature (25- 40 oC),and percentage inoculums (5- 15 %v/v) on ethanol yield were assessed by using 24 full factorial design (FFD) and validated statistically by analysis of variance (ANOVA).The optimum temperature is 25.29 celcius and optimum inoculum size is 10.54 % .Saccharomyces cerevisiae Kyokai 7 produced 41.43% higher ethanol compared to S.cerevisiae.The mean percentage error is 10.32 in screening parameter experiment.The influence of temperature was found to be more pronounced on ethanol yield compare to others parameter